Financial analysis of Chir pine plantations for carbon offsets, timber and resin in Nepal - KC, B; Stainback, G. A. (Banko Janakari, 2013)
A financial analysis was done for Chir pine (Pinus roxburghii) plantations that produce carbon offset payments, timber and resin in a community forest context in Nepal. Results indicate that the inclusion of carbon offset payments increases rotation age and land expectation value. The optimal rotation age is approximately 35 years without including carbon offset payments, while the rotation age can increase beyond 75 years with the inclusion of carbon offset payments. The substantial change in optimal rotation age also suggests that carbon offset payments will likely change the product mix produced from Chir pine plantations. Likewise, land expectation value increases significantly with carbon offset payments indicating that local communities could benefit from such payments. The results also indicate that different assumptions about the quantity of long term carbon storage (i.e. pickling rate) have a significant impact on rotation age and land expectation value. DOI: http://dx.doi.org/10.3126/banko.v22i2.9193 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page: 3-10 Uploaded date: 12/1/2013